2000
DOI: 10.4049/jimmunol.164.4.1881
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Cyclin D1 in Thymic Epithelial Precursors Promotes Epithelial and T Cell Development

Abstract: We previously reported that precursors within the keratin (K) 8+5+ thymic epithelial cell (TEC) subset generate the major cortical K8+5− TEC population in a process dependent on T lineage commitment. This report demonstrates that expression of a cyclin D1 transgene in K8+5+ TECs expands this subset and promotes TEC and thymocyte development. Cyclin D1 transgene expression is not sufficient to induce TEC differentiation in the absence of T lineage-committed thymocytes because TECs from both hCD3ε transgenic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 31 publications
(31 reference statements)
5
54
0
Order By: Relevance
“…Most cells express cytokeratins 8 and 18, but a distinct subset also express cytokeratin 5. This subset contains precursors that generate the major population of cytokeratin 5-negative cortical epithelial cells (7,45). Our studies show that, in the hypoplastic thymus of mice deficient for FgfR2-IIIb, many of the epithelial cells fail to progress from the cytokeratin 5/cytokeratin 18-positive stage (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Most cells express cytokeratins 8 and 18, but a distinct subset also express cytokeratin 5. This subset contains precursors that generate the major population of cytokeratin 5-negative cortical epithelial cells (7,45). Our studies show that, in the hypoplastic thymus of mice deficient for FgfR2-IIIb, many of the epithelial cells fail to progress from the cytokeratin 5/cytokeratin 18-positive stage (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The present study demonstrates that distinct thymocyte subsets are responsible for changes in the expression patterns of K5 and IL-7 in cortical TECs of the postnatal thymus. We previously demonstrated that downregulation of K5 in the thymic cortex depends on cross talk between K8 ϩ K5 ϩ TEC precursors and T lineage-committed thymocytes (45,67). Thus, K5 is down-regulated in the well-organized cortex of RAG-1-deficient mice, whereas human CD3⑀ transgenic and RAG2/␥ c Ϫ/Ϫ thymi that sustain earlier blocks in thymopoiesis retain a primitive, poorly organized TEC population consisting of K8 ϩ K5 ϩ TEC progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…In a thymic epithelial cell study, transgenic expression of cyclin-D1, one of the principal target genes of Wnt signalling, has lead to the expansion of the entire epithelial compartment (Klug et al 2000) suggesting that canonical Wnt signalling is involved in thymic epithelial cell proliferation, strengthening the argument, that thymic epithelial development is regulated by Wnt-s. So far, signalling studies have revealed, that Wnt4 can activate both the canonical (Lyons et al 2004) and the non-canonical (Torres et al 1996) (Chang et al 2007;Kim et al 2009) Wnt-pathways.…”
Section: Wnt-s In the Thymusmentioning
confidence: 99%